Dynamic control of working slope shape and optimization of advance speed in seasonally stripped open-pit coal mine - Guangwei LIU; Yunlong HUANG; Bo CAO; Yong YAO (Meitan kexue jishu, 2023)
Due to the discontinuity of the stripping project in seasonal stripping open-pit coal mines, the untimely advance distance of the working slope is huge. In order to reduce the advance stripping and save the stripping distance, research was carried out on dynamic control of the shape of the working slope and optimization of the limit advance speed of the working slope in seasonal stripped open-pit coal mines. This paper explains the shape and operation procedure of the working slope in seasonal stripped open-pit coal mines and analyzes factors that influence working slope shape and advance speed. Based on structural form of working slope and stripping operation mode of seasonally stripped open-pit coal mines, an engineering model for shape optimization of working slope is established. The relationship between circular advance distance of working slope with working bench width and exposed coal mode of stope is discussed. Bench group cycle advance engineering quantity and production capacity of layered equipment, advance time of the working slope cycle and calculation method for reliability of side slope transportation system are given. With optimization goal of minimizing transport work of stripping material and time-space continuity of stripping engineering as constraint condition, mathematical model for shape optimization of working slope in seasonally stripped open-pit coal mine is established. Sequential quadratic programming algorithm (SQP) is introduced to solve nonlinear programming. A method to realize dynamic control of shape of working slope of seasonally stripped open-pit coal mine by determining combination mode of stripping benches and working bench width and a method to optimize limit advance speed of stripped working slope are proposed. Taking Shengli West No.2 Open-pit Coal Mine as an engineering background, above-mentioned optimization control method is applied for research and calculation and solution are carried out by establishing form optimization model of stripping working slope and substituting actual parameters of West No.2 Open-pit Mine. Results show that when the number of benches in bench group is 5 and working bench width is 89 m, advance of working slope meets the requirements of space-time continuity in stripping engineering and transport work of stripped objects is smallest. In this shape, limit advance speed of the working slope is 320 m/a, and change of limit advance speed of the working slope is analyzed and determined when combination of benches and cyclic advance distance is changed.